Pengaruh Sustainability Reporting Terhadap Kinerja Keuangan Perusahaan Publik dari Sisi Asset Management Ratios - Lesmana, Yuliani (Business Accounting Review, 2014)
Sustainability Reporting in an indirect infuence on the companys assets and the sale of the company. The efficiency of asset management companies to generate sales can be measured by the ratio of asset management. Therefore, this study aimed to know the affect of sustainability reporting on the financial performance, especially on the asset management ratios. The sample used was a public companies in Indonesia, which published the report Sustainability Report at the National Center for Sustainability Reporting and on each companys website of the consecutive year of 2009-2011, as well as published their annual financial statements on the Indonesia Stock Exchange and on the website of each company consecutive year of 2010-2012. By using SEM-PLS analysis method, the disclosure of sustainability reporting indicators (Indicator SR) based on the GRI - G3 Guidelines were grouped into three aspects, which were economic, social and environmental as independent variables and financial performance were the ratio of asset management (Inventory Turnover ratios, receivables Turnover ratios, Net Working Capital Turnover ratios, Fixed Asset Turnover ratios, Total Asset Turnover ratios) as the dependent variables. As a result, sustainability reporting in the economic and environmental aspects gave significant negative affect on improvement Ratio Asset Management, mean while in the social aspects, sustainability reporting gave significant positive affect on the improvement of Ratio Asset Management.